One more step in the methods of integration of sinn ax - (:unkn) unknown (My University, 1993)
In this paper, a linear compact formula for the evaluation of the integral of sinn ax is presented. This new formula requires much less effort compared to the reduction formulae given in the literature. The organization of this paper is as follows. The formulae currently available for the evaluation of the integral sinn ax are reviewed in the introduction. The new formula is derived in Section 2 and then extended to the evaluation of the integral of sinn ax cosm ax in the conclusion. © 1993 Taylor and Francis Ltd.